Penggunaan Media Iklan Youtube Kemenkes dalam Pembelajaran Keterampilan Menulis Karangan Persuasi - Ningsih, Wahyu; Hindun (UIN Raden Mas Said Surakarta, Indonesia, 2022)
Media is an important instrument for teachers in teaching and learning activities. The existence of media is expected to make it easier for teachers to convey material and make it easier for students to understand the material, of course the media used must be adapted to the development of the times. This study aims to find out how the use of video media from the Ministry of Health's YouTube channel in learning persuasive text writing skills for class VIII students at SMP Islamiyah Ciputat. The method used in this study is a qualitative descriptive method in the form of a description of the results of student essays. The data collection techniques used in this study used observation, interviews, documentation, and tests. Aspects assessed in this study were the quality of the content of the essay, spelling and writing, structure of the essay, organization of content, and accuracy of diction. The results of the study showed that the ability to write persuasive essays for class VIII-3 students obtained an average score of 81, 30 with good category (B). So it can be concluded that, public service advertising media from the Ministry of Health's YouTube can be used as an appropriate learning media for learning the skills of writing persuasive essays. Media menjadi insturmen yang penting bagi guru dalam kegiatan belajar mengajar.Adanya media diharapkan memudahkan guru menyampaikan materi dan memudahkan peserta didik dalam memahami materi, tentunya media yang digunakan harus disesuaikan dengan perkembangan zaman.Penelitian ini bertujuan untuk mengetahui bagaimana penggunaan media video dari kanal YouTube Kemenkes dalam pembelajaran keterampilan menulis teks persuasi pada siswa kelas VIII di SMP Islamiyah Ciputat.Metode yang digunakan dalam penelitian ini ialah metode deskriptif kualitatif yang berupa pendeskiripsian dari hasil karangan siswa.Adapun teknik pengumpulan data yang digunakan dalam penelitian ini menggunakan teknik observasi, wawancara, dokumentasi, dan tes.Aspek yang dinilai dalam penelitian ini yakni kualitas isi karangan, ejaan dan tata tulis, struktur karangan, organisasi isi, dan ketepatan diksi.Hasil pada penelitian menunjukkan bahwa keterampilan menulis karangan persuasi peserta didik kelas VIII-3 memperoleh nilai rata-rata 81, 30 dengan kategori baik (B).Jadi dapat disimpulkan bahwa, media iklan layanan masyarakat dari YouTube Kemenkes dapat dijadikan media pembelajaran yang sesuai untuk pembelajaran keterampilan menulis karangan persuasi.